2016
DOI: 10.1177/0960327116660864
|View full text |Cite
|
Sign up to set email alerts
|

Allicin ameliorates kidney function and urinary bladder sensitivity in cyclosporine A-treated rats

Abstract: Cyclosporine-A (CsA) is an immunosuppressive drug which has been used to prevent rejection after organ transplantation and to treat certain autoimmune diseases. However, its therapeutic use is limited by nephrotoxicity. In this study, the modulator effect of allicin on the oxidative nephrotoxicity of CsA in rats was investigated. Furthermore, the effect of allicin on CsA-induced hypersensitivity of urinary bladder rings to acetylcholine (ACh) was estimated. Rats were divided into three groups, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Growing evidence has shown that an overproduction of ROS, combined with inefficient antioxidant defenses in response to oxidative stress, is implicated in nephrotoxicity caused by CsA, leading to renal dysfunction (increased UP, BUN, and SC, and decreased CCr). [ 21,26,27 ] Studies have shown that CsA‐induced ROS production mediates renal tubular cell apoptosis, tubulointerstitial fibrosis, and arteriopathy. [ 28 ] Li et al [ 29 ] found that CsA decreased the activity of SOD and GSH, which induced the pathogenesis of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence has shown that an overproduction of ROS, combined with inefficient antioxidant defenses in response to oxidative stress, is implicated in nephrotoxicity caused by CsA, leading to renal dysfunction (increased UP, BUN, and SC, and decreased CCr). [ 21,26,27 ] Studies have shown that CsA‐induced ROS production mediates renal tubular cell apoptosis, tubulointerstitial fibrosis, and arteriopathy. [ 28 ] Li et al [ 29 ] found that CsA decreased the activity of SOD and GSH, which induced the pathogenesis of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples were centrifuged for 15 minutes at 3000 rpm for subsequent analysis of urinary protein (UP) and creatinine clearance (CCr). [ 21 ] At the end of the experiment, body weight was recorded and mean arterial pressure (MAP) was measured and analyzed using the BL‐420S biological signal analytical system (Taimeng Technology Co Ltd, Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Ccr (ml/min) = [urinary Cr (mg/dl) × urine volume (ml) x 1440/serum Cr (mg/dl)] 1440: total number of minutes per day. [ 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…Glomerular filtration was indicated by deducing creatinine clearance (Ccr) by applying the following equation: Ccr (ml/min) = [urinary Cr (mg/dl) × urine volume (ml) x 1440/ serum Cr (mg/dl)] 1440: total number of minutes per day. [15] 2.5 | Determination of antioxidant status MDA was estimated in accordance with the method of Ohkawa et al [16] The principle based upon its reaction with thiobarbituric acid and the obtained color was measured by a spectrophotometer at 532 nm. GSH was evaluated in accordance with the method of Ellman.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…One of the major sources of intracellular reactive oxygen species in mitochondria. Thus, these organelles are linked to cyclosporin A (CSA) renal toxicity [8].…”
Section: Introductionmentioning
confidence: 99%